Preliminary standardized catch rates in number of fish by age for the south Atlantic swordfish (Xiphias gladius) of the Spanish longline fleet, for the period 1989-2011 assuming a tentative growth model - Mejuto-García, Jaime; Ramos-Cartelle, Ana; García-Cortés, Blanca (2014)
Trials of standardized catch rates in number of fish by age were done using log-normal General Linear Modeling (GLM) from trips carried out by the Spanish surface longline fleet in the South Atlantic swordfish stock. Indices were developed for a 23 years period (1989-2011) for ages ranging from 1 to 5+, assuming the Gompertz’s sex-combined growth model of the North Atlantic swordfish as a proxy for ageing the size data per trip. The criteria used to define areas, time periods and models were similar to those used to develop the biomass index, including information such as gear style, a target variable and bait type. The models explained between 29% and 66% of the CPUE variability. Despite the growth assumptions used, the trials show significant diagnoses and quite stable trend over time of the standardized CPUEs by age obtained.